Participação da área septal medial nas respostas sialogoga, dipsogênica e cardiovascular induzidas pela pilocarpina - Paulin, Renata Fabris (Universidade Federal de São Carlos, 2008)
Peripheral injection of pilocarpine (PILO, 1 mg/Kg of body weight), muscarinic cholinergic agonist, induce salivation, water intake and pressor response. The medial septal area (MSA) is an important brain area involved in cardiovascular regulation and hydroelectrolytic control. In this present study, we investigated: 1) the effect of MSA electrolytic lesion or the blockade of muscarinic cholinergic receptors into MSA on salivation, water intake and cardiovascular responses induced by peripheral pilocarpine; 2) the role of the sympathetic nervous system and/or vasopressin on the cardiovascular responses induced by peripheral pilocarpine; 3) the effect of injection of pilocarpine into MSA on salivation, water intake and cardiovascular responses. Male Holtzman rats weighing 280 to 320 g were submitted to 1 or 15 days MSA electrolytic lesion (2 mA x 5 s) or stainless steel guide cannulas were stereotaxically implanted into the MSA. We observed that peripheral pilocarpine (1 mg/kg of body weight) induces salivary secretion, water intake and an increase in mean arterial pressure (MAP) . This increase in MAP is due to an activation of simpathetic nervous system, since it was significantly reduced by previous treatment with prazosin (1 mg/kg of body weight), but not by vasopressin V1a receptor antagonist (10 µg/kg of body weigh). The salivary secretion and dipsogenic response induced by peripheral pilocarpine was reduced by MSA eletrolytic lesion or MSA muscarinic cholinergic blockade. Nonetheless, the pressor response induced by peripheral pilocarpine was not depend of MSA, since MSA eletrolytic lesion or muscarinic cholinergic receptors blockade did not change this response. Pilocarpine injection into MSA induced water intake (200 e 500 nmol/0,5 µL), salivary secretion (500 nmol/0,5 µL) and MAP increase (500 nmol/0,5 µL). Our results show that peripheral or MSA injection of pilocarpine induce salivary secretion, water intake and pressor response. The pressor response induced by peripheral pilocarpine is due to sympathetic activation. The MSA and its muscarinic cholinergic receptors are involved in the salivary secretion and water intake, but not in the control of pressor response induced by peripheral pilocarpine, suggesting that MSA has a differencial control on the responses induced by peripheral pilocarpine.
Keywords: Fisiologia; Área septal; Salivação; Pressão arterial; Ingestão de água; Pilocarpina; CIENCIAS BIOLOGICAS::FISIOLOGIA